Tipologi Perubahan Citra Agnes Mo: Kajian Perspektif Psikologi Komunikasi - Meliala, Robbikal Muntaha (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2018)
Agnes Monica as a common human has surely changed in her life naturally. In her context as an entertainer, she has surely changed either in her self concept, start from her performance, her mind and her style of achievement. Branding of â€œAgnes Monicaâ€ change to be â€œAgnez Moâ€ would be main thesis of this research. The author has tried to classify her image as an international singer seemed from perspective of communication psychology. Based on Theory of Function by Katz (1960), Psychology of Cognitive Movement, Agnez Moâ€™s act referenced from 4 main reason, Act as Instrumental Function, Act as Defense Mechanism Tool, Act as Object Receiver and Encode the Meaning, and Act as Value of Self Expression in Answering One Situation. Research Methodology: Descriptive Qualitative by Documentation and Study of Literature. Conclusion Â : Changed Typology of Agnez Moâ€™s Image as an International Singer consist of Natural Changed Typology, Planned Changed Typology, Readiness to Change of Typology , Alterative Movement and Redemptive Movement.Â Keywords : Changed, Image, Agnez Mo, Communication Psychology.